Stability Evaluation of Palm Oil Mill Effluent Treatment in a Single Feeding Systems Through Temperature, VFA, and Alkalinity Monitoring: Evaluasi Stabilitas Sistem Pengolahan Limbah Cair Kelapa Sawit Single Feeding Melalui Pemantauan Suhu, VFA, dan Alkalinitas - Renjani, Rengga Arnalis; Dwi Dharmawati, Nuraeni; Ramadhani, Sisca (Universitas Djuanda, 2025)
Palm Oil Mill Effluent (POME) is one of the most critical environmental concerns in the palm oil industry due to its high organic load and strongly acidic nature. Improper management of POME poses significant risks to aquatic ecosystems and soil quality. This study aimed to evaluate the biological stability of a single feeding POME treatment system by monitoring temperature, pH, volatile fatty acids (VFA), and total alkalinity (TA) across a 21-day observation period at each treatment pond. Parameters were measured sequentially from the effluent outlet to the final sedimentation pond. The results showed a gradual decrease in temperature from 63°C to 27–30°C, with a corresponding increase in pH from 4.23 to 7.86, indicating successful neutralization. VFA concentrations ranged from 458–474 mg/L, while TA remained within 2.40–2.57, resulting in a VFA/TA ratio consistently below 0.4. These values confirmed that the system operated under biologically stable conditions. The study concluded that monitoring these parameters offers a simple, cost-effective method for assessing the operational performance of open-lagoon POME treatment systems. Scientifically, this research contributes to the development of practical tools for real-time wastewater monitoring in agro-industrial applications. Environmentally, it supports safer and more sustainable land application of treated POME, reducing the risk of pollution and promoting better resource recovery practices.